Is blood eosinophilia a good predictor of severity for CRS? - Penêda, José Ferreira (2020)
Introduction: Chronic rhinosinusitis (CRS) is a growing diagnosis in the western population. Functional Endoscopic Sinus Surgery (FESS) is performed when disease is not controlled with medical therapy alone. Despite the high frequency of this pathology and surgery, studies on postoperative disease control are rare and predictive models based on clinical data are lacking. The role of blood eosinophilia as a marker of disease severity has recently been demonstrated in different populations. Objectives: The authors investigated the correlation between eosinophilia, disease severity and post-operative control on CRS. Materials and methods: A retrospective analysis was performed with patients undergoing FESS from January 1st, 2015 to October 31st, 2017. Demographic, analytical and imaging data were collected and analysed using the IBM SPSS Statistics 25® statistical software. Results: 184 patients undergoing FESS were included; Those not associated with CRS - mucoceles, neoplasms, fungal RS, oro-antral fistulas, dacryocystorhinostomies, sphenopalatine artery ligations - as well as patients with co-morbidities predisposing to CRS (ciliary dyskinesia, cystic fibrosis) were excluded. 108 patients were considered eligible for this study. 60% were males. The authors investigated the association of blood eosinophilia value with CRS type (with or without polyps), postoperative disease control, patient-reported symptomatology, surgical extent, rhinitis or asthma, smoking and the prevalence of tissue eosinophils. Conclusion: Blood eosinophilia may be a marker of severity in some forms of chronic rhinosinusitis. The subdivision of CRS into inflammatory clusters is essential to identify which markers are adequate to predict disease severity.